La Mobilité Commerciale du Bétail entre le Sahel et les pays Côtiers: L'avenir du Convoyage à Pied. (31st December 2012) - Corniaux, Christian; Thébaud, Brigitte; Gautier, Denis
Abstract : This paper debates the future of long-distance commercial trekking of cattle, from Sahelian countries to the terminal markets on the coast. In the general context of shrinking access to pastoral resources, and constraints affecting livestock mobility throughout West Africa, this time-honoured form of export is being called into question by national governments and local authorities. Road transport of live animals and the reintroduction of refrigerated-meat value-chains are increasingly being proposed as better alternatives. Based on field research conducted within the framework of an EU funded regional programme, the authors challenge this vision and conclude that trading cattle on the hoof retains optimal levels of efficiency, especially in the trade of young animals as they actually gain weight 'for free' during the deliberately slow-paced journey which may last several months. In comparison, road transport remains heavily constrained by poor infrastructure, limited availability of vehicles and high transport related costs – including non-physical barriers. Support for on-the-hoof cattle trade through national and regional policies will be crucial if the competitiveness of the Sahelian beef-export value-chain is to be strengthened in a context of growing urban demand for meat, declining consumer purchasing power and strong competition from other animal protein sources (fish, chicken and imported meat).